Психолого-педагогическое сопровождение ребенка с аутистическими нарушениями как реализация личностно ориентированного подхода - Рыбченко, Л. К.
Recently, correctional pedagogy and psychology in Ukraine is determined by the priority development trends rehabilitation inclusive content correction - pedagogical work and habilitation of children “at risk”. De© ite the complications in the inclusive inst itutions, more and more children with mental and physical disabilities are involved in remedial work within inclusive education and upbringing. This suggest s that the inclusion of children with autism in a comprehensive training syst em can be successful and contribute to their psychological and emotional development.The article raises the problem of psycho-pedagogical support of the child with autism. The data public survey about the problems faced by families, where children with autism. Designated conditions and presents a model of successful and productive work on the psychological and pedagogical support of a multidisciplinary team of a child with autism .
Keywords: Аутизм